2015
DOI: 10.1371/journal.pmed.1001890
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Pharmacologically Induced Immunosuppression by Immune Repertoire Sequencing to Detect Acute Allograft Rejection in Heart Transplant Patients: A Proof-of-Concept Diagnostic Accuracy Study

Abstract: BackgroundIt remains difficult to predict and to measure the efficacy of pharmacological immunosuppression. We hypothesized that measuring the B-cell repertoire would enable assessment of the overall level of immunosuppression after heart transplantation.Methods and FindingsIn this proof-of-concept study, we implemented a molecular-barcode-based immune repertoire sequencing assay that sensitively and accurately measures the isotype and clonal composition of the circulating B cell repertoire. We used this assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…This observation raises the question of whether TTV load can be used to gauge immunocompetence. Consistent with this hypothesis are recent studies demonstrating the association between TTV viral loads and rejection (16*, 18*) (Figure 1) as well as opportunistic infection. (19)…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…This observation raises the question of whether TTV load can be used to gauge immunocompetence. Consistent with this hypothesis are recent studies demonstrating the association between TTV viral loads and rejection (16*, 18*) (Figure 1) as well as opportunistic infection. (19)…”
Section: Introductionsupporting
confidence: 82%
“…(18*) The antibody heavy chain IGH transcript is unique as its expression changes in abundance and in sequence when a B cell is activated. Activated B cells express high levels of mutated antibodies of the IgG and IgA isotypes, while naïve B cells express non-mutated IgM antibodies at low levels.…”
Section: Introductionmentioning
confidence: 99%
“…The human immune system relies on highly diverse and complex receptors to protect us from a wide array of pathogens. The transcripts encoding these immune receptors are of great interest to basic and translational research as well as diagnostic and other clinical purposes 5,11,12 . However, RNA-seq, the current gold-standard for whole transcriptome analysis, fails short of describing these immune receptors completely and accurately 7 .…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput DNA sequencing of immunoglobulin genes has been used to detect and follow residual disease in B cell malignancies, determine vaccine response, and perhaps has a role in autoimmune disease diagnostics [1620]. We reported that repertoire sequencing is correlated with immune activity during rejection episodes in heart transplant recipients [21]. …”
Section: Introductionmentioning
confidence: 99%